Ketahanan Nasional Dalam Perspektif Al-qur’an - Ghani, Abdul (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2020)
The conclusion of this dissertation is that the concept of national resilience in the Qur'an supports the National Resilience concept of national resilience, which consists of 8 (eight) gatra, namely: geography, demographics, ideology, politics, economics, social culture, and natural resources. Besides that, through searching the words al-difa '(defense), al-amn (security), al-hifz (maintenance) and al-salam (safety in the Qur'an, this dissertation reveals 9 (nine) other gatras that support the national resilience, namely: conducive community environmental resilience, the community's physical and mental health, the quality of education, law enforcement, deliberative culture, technology, national character, leadership and faith of citizens.This disertation has different studies with Syarifuddin (2018): "Soldiers in the Qur'anic Perspective", which discusses the function of the army as guardians of national resistance in the perspective of the Koran. Thus with Muhammad Yahdi (2019): "Military in the perspective of the Koran", which discusses the mental development of the army with an approach used by Rasulullah Saw in mentoring the army as a guardian of national defense. This dissertation has the same opinion with Chasib (2015), Valentinus CP. (2014) Lotaria L atif (2017) which discusses global national resilience. This dissertation has a difference with Fitriyani from Gadjah Mada University in Yogyakarta (2015) entitled "Care for the Environment in the framework of national resilience", Study on the youth association of Environmental care in the Semarang area.This dissertation uses a qualitative method, whereas in interpretation, the writer uses the maudu'i interpretation method by extracting verses of the Koran as an argument to answer various reasons related to the title namely: "National resilience in the perspective of the Koran".